2022
DOI: 10.3389/fpubh.2022.1012998
|View full text |Cite
|
Sign up to set email alerts
|

Application of oXiris-continuous hemofiltration adsorption in patients with sepsis and septic shock: A single-centre experience in China

Abstract: oXiris is a new, high-adsorption membrane filter in continuous hemofiltration adsorption to reduce the inflammatory response in sepsis. The investigators retrospectively reviewed patients with sepsis/septic shock who underwent at least one oXiris-treatment from November 2020 to March 2022. The demographic data, baseline levels before treatment, clinical datas, prognosis, and the occurrence of adverse events during treatment were recorded. 90 patients were enrolled in this study. The hemodynamic indices, sequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 55 publications
(82 reference statements)
0
4
0
Order By: Relevance
“…The reduction of thrombocyte count was not constantly described in the literature. Schwidenhammer et al [15] did not report a thrombocyte count reduction, while others reported a significant decrease over time [17, 20, 27]. However, the real clinical impact of such reduction is unknown in the absence of bleeding.…”
Section: Discussionmentioning
confidence: 99%
“…The reduction of thrombocyte count was not constantly described in the literature. Schwidenhammer et al [15] did not report a thrombocyte count reduction, while others reported a significant decrease over time [17, 20, 27]. However, the real clinical impact of such reduction is unknown in the absence of bleeding.…”
Section: Discussionmentioning
confidence: 99%
“…It attracted much attention for using extracorporeal adsorption to remove inflammatory mediators from the bloodstream [ 11 , 12 ]. In 2018, a study showed that the hemodynamic and respiratory parameters were improved in ten children with sepsis after they received the lipopolysaccharide-adsorption course by hemoperfusion with PMX [ 13 ]. Also, a case series showed that it might be an efficacious and relatively safe adjunctive treatment for hemoperfusion with HA330 cartridges to clear the cytokine storm in children with sepsis [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…It showed that CRRT with the oXiris membrane set improved patient outcomes with a reduction of vasopressors and a downregulation in blood inflammatory mediators [ 12 ]. Another study also found that CRRT with the oXiris membrane may decline the lactate level and infection indicators [ 13 ]. However, a study that enrolled 136 patients showed no difference in 90-day mortality in the oXiris group and the ST150 group, although the oXiris group had lower 7-day and 14-day mortality [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Various types of extracorporeal blood purification treatments have recently been introduced to remove excess cytokines and endotoxins. One type, AN69-oXiris (Gambro Industries, Meyzieu Cedex, France), is a filter that can remove both endotoxin and cytokines and also has a fluid removal function for continuous renal replacement therapy (CRRT) ( 2 , 3 ). However, concerns have been raised that its endotoxin removal might be insufficient for patients with severe septic shock and high endotoxin concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…Septic shock is the leading cause of mortality in critically ill patients, with a high mortality rate of 25-30% despite aggressive resuscitation and intensive care of these patients (1)(2)(3)(4)(5). One of the major factors contributing to fatal outcomes is the dysregulated immune response during septic shock.…”
Section: Introductionmentioning
confidence: 99%